2016
DOI: 10.1128/mcb.00861-15
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Long Intergenic Noncoding RNAs: High Promoter Conservation and Dynamic, Sex-Dependent Transcriptional Regulation by Growth Hormone

Abstract: Long intergenic noncoding RNAs (lincRNAs) are increasingly recognized as key chromatin regulators, yet few studies have characterized lincRNAs in a single tissue under diverse conditions. Here, we analyzed 45 mouse liver RNA sequencing (RNA-Seq) data sets collected under diverse conditions to systematically characterize 4,961 liver lincRNAs, 59% of them novel, with regard to gene structures, species conservation, chromatin accessibility, transcription factor binding, and epigenetic states. To investigate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(96 citation statements)
references
References 118 publications
2
91
0
Order By: Relevance
“…Liver-expressed lincRNA promoters show greater enrichment for proximal binding of liver transcription factors than protein-coding gene promoters, which may reflect the higher conservation of liver lincRNA promoters (Melia et al, 2016). In fact, recently, hepatic lncRNAs are reported to be involved in the progression of liver fibrosis (He et al, 2014;Yu et al, 2016;Zheng et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Liver-expressed lincRNA promoters show greater enrichment for proximal binding of liver transcription factors than protein-coding gene promoters, which may reflect the higher conservation of liver lincRNA promoters (Melia et al, 2016). In fact, recently, hepatic lncRNAs are reported to be involved in the progression of liver fibrosis (He et al, 2014;Yu et al, 2016;Zheng et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A set of 24,197 annotated mouse RefSeq genes (which includes some RefSeq lncRNAs) and a set of 15,558 liver-expressed lncRNA genes (Lodato et al, 2017;Melia and Waxman, 2019) was considered for differential expression analysis. These lncRNAs include intergenic lncRNAs, as well as lncRNAs that are antisense or intragenic with respect to RefSeq genes, and were discovered using a computational pipeline for lncRNA discovery described elsewhere (Melia et al, 2016) based on 186 mouse liver RNA-seq datasets representing 30 different biological conditions. RefSeq and lncRNA genes that showed significant differential expression following exposure to WY-14643 were identified by EdgeR as outlined elsewhere (Melia et al, 2016).…”
Section: Analysis Of Sequencing Resultsmentioning
confidence: 99%
“…PPARA-dependent lncRNAs identified by RNA-seq were selected and mRNA levels monitored over a 24 hour period after WY-14643 treatment, revealing that lncRNA expression profiles paralleled those of known protein-coding PPARA target genes (Figure S1A-D). As lncRNA expression is often highly tissue specific (Iwakiri et al, 2017;Melia et al, 2016;Perron et al, 2017), the relative basal levels were measured for PPARA-responsive lncRNAs expressed in oxidative tissues that utilize fatty acids as an energy source and express PPARA at the highest levels. Ppara mRNA and its classic target gene Cyp4a14 served as controls.…”
Section: Lncrna Regulation By Ppara Is Highly Tissue-specificmentioning
confidence: 99%
See 1 more Smart Citation
“…The health impacts of sex differences in liver include a higher incidence of aggressive liver cancer in males [5], increased susceptibility to autoimmune hepatitis in females [6], and sex differences in metabolism of some pharmaceuticals and environmental chemicals [7]. Transcriptomic and epigenetic sex-bias is best characterized in mouse liver, where ~1,000 genes [8], including many lncRNA genes [9,10] and miRNAs [11], exhibit sex-biased expression that may be regulated by thousands of sex-specific DNase I hypersensitive sites (DHS) [12,13]. This prior work has shown that the majority of sex-biased genes do not have geneproximal sex-biased chromatin marks or DHS, suggesting most epigenetic sex bias occurs at distal elements such as enhancers [12,13].…”
Section: Introductionmentioning
confidence: 99%